Whole body composition analysis by the BodPod air-displacement plethysmography method in children with phenylketonuria shows a higher body fat percentage - Albersen, Monique (Springer Netherlands, 2010)
BACKGROUND: Phenylketonuria (PKU) causes irreversible central nervous system damage unless a phenylalanine (PHE) restricted diet with amino acid supplementation is maintained. To prevent growth retardation, a protein/amino acid intake beyond the recommended dietary protein allowance is mandatory. However, data regarding disease and/or diet related changes in body composition are inconclusive and retarded growth and/or adiposity is still reported. The BodPod whole body air-displacement plethysmography method is a fast, safe and accurate technique to measure body composition. AIM: To gain more insight into the body composition of children with PKU. METHODS: Patients diagnosed with PKU born between 1991 and 2001 were included. Patients were identified by neonatal screening and treated in our centre. Body composition was measured using the BodPod system (Life Measurement Incorporation©). Blood PHE values determined every 1–3 months in the year preceding BodPod analysis were collected. Patients were matched for gender and age with data of healthy control subjects. Independent samples t tests, Mann–Whitney and linear regression were used for statistical analysis. RESULTS: The mean body fat percentage in patients with PKU (n = 20) was significantly higher compared to healthy controls (n = 20) (25.2% vs 18.4%; p = 0.002), especially in girls above 11 years of age (30.1% vs 21.5%; p = 0.027). Body fat percentage increased with rising body weight in patients with PKU only (R = 0.693, p = 0.001), but did not correlate with mean blood PHE level (R = 0.079, p = 0.740). CONCLUSION: Our data show a higher body fat percentage in patients with PKU, especially in girls above 11 years of age.